2008
DOI: 10.1063/1.3032512
|View full text |Cite
|
Sign up to set email alerts
|

Impedance spectroscopy and optical characterization of polymethyl methacrylate/indium tin oxide nanocomposites with three-dimensional Voronoi microstructures

Abstract: This study describes the optical and ac electrical characterization of polymethyl methacrylate (PMMA)/indium tin oxide (ITO) nanocomposites containing a Voronoi-type segregated network microstructure. Optical transmission microscopy, scanning electron microscopy (SEM), and impedance spectroscopy were used to investigate the microstructure and electrical properties of the composites. The complex refractive index values of the composites were measured by using a modified version of the internal reflection intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 42 publications
0
30
0
Order By: Relevance
“…[22][23][24] During this shape transformation, ATO NPs were primarily forced to be aligned along the edges to form percolation networks, while quite a number of ATO NPs still occupied the interfaces. In the composites with the filler content slightly below the percolation threshold (Figs.…”
Section: A Phase Segregated Microstructures In Pmma/ato Compositesmentioning
confidence: 99%
“…[22][23][24] During this shape transformation, ATO NPs were primarily forced to be aligned along the edges to form percolation networks, while quite a number of ATO NPs still occupied the interfaces. In the composites with the filler content slightly below the percolation threshold (Figs.…”
Section: A Phase Segregated Microstructures In Pmma/ato Compositesmentioning
confidence: 99%
“…Still a lot of controversy exists which requires serious attention. Previous reports in literature showed that the value of P C depends on various parameters, such as, size, shape, spatial distribution, adhesiveness, viscosity, wetting of the polymer, polymer matrix, process conditions, etc 1–8, 11–26. This has motivated us to consider a systematic study to optimize P C as a function of various parameters, such as, materials processing conditions, shape and size of the fillings, rheological properties of the matrix, etc.…”
Section: Introductionmentioning
confidence: 63%
“…(1) to the conductivity data for 0.40 sample shows that the value of n was found to be 0.78 which is well within the Johnscher's universal value of between 0 and 1 36. The frequency which separates the region of ac and dc conductivity region is called critical frequency or hopping frequency ( f c ) 25. The critical frequency is normally determined by locating the intersection of the lines that are tangent to the frequency‐dependent and frequency‐independent regions.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations